2007
DOI: 10.1111/j.1439-0426.2007.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the substrate preference of white sturgeon (Acipenser transmontanus) eleutheroembryos

Abstract: Fifty white sturgeon (Acipenser transmontanus) eleutheroembryos (average size 0.17 g) were placed onto each of four quadrants (0.45 m 2 quadrant )1 ; 200 fish tank )1 ) of different sized substrates in four circular tanks (approximately 562 L). Each of three quadrants had a different size substrate and the fourth quadrant was left bare. We used one replicate of smaller size substrates (0.5-11.9 mm) and one replicate of larger size substrates (21.7-88 mm). It was found that the white sturgeon eleutheroembryos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
0
27
0
1
Order By: Relevance
“…Two substrate treatments were used: gravel (3 cm depth) and no substrate (bare conditions). The gravel substrate and the grain size used were based in part on the findings of a white sturgeon YSL substrate preference study by Bennett et al (2007) and from results of my previous work (Boucher and McAdam, unpublished). A mixture of gravel was used ranging from pea gravel to 2 cm gravel (11.9 -21.7 mm in longest axis).…”
Section: Experimental Tanksmentioning
confidence: 99%
See 4 more Smart Citations
“…Two substrate treatments were used: gravel (3 cm depth) and no substrate (bare conditions). The gravel substrate and the grain size used were based in part on the findings of a white sturgeon YSL substrate preference study by Bennett et al (2007) and from results of my previous work (Boucher and McAdam, unpublished). A mixture of gravel was used ranging from pea gravel to 2 cm gravel (11.9 -21.7 mm in longest axis).…”
Section: Experimental Tanksmentioning
confidence: 99%
“…While habitat requirements of larval sturgeon are unclear, there is increasing evidence that gravel substrate is important during early developmental stages. Bennett et al (2007) found that larval white sturgeon showed a preference for gravel substrates soon after hatching. Other studies have also shown that in both lab and riverine conditions, sturgeon larvae rear in gravel (Gessner et al 2009;McAdam 2011) and perform better in terms of growth and survival when provided with gravel substrate (Chapter 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations